Odpowiedzi

Najlepsza Odpowiedź!
2010-02-19T10:31:48+01:00
Jako mnożenie będę wpisywać * (gwiazdkę)

dokładnie rozpisane:

a )2a²-4 dla a= ½
2 * (1/2)² - 4 = 2 * 1/4 - 4 = 1/2 - 4 = -3 i 1/2 czyli 3,5



b) (½ a + 2b ) × (-3) dla a= -4 dla b = ½
[1/2 * (-4) + 2 * 1/2] * (-3) = [(-2) + 1] * (-3) = (-1) * (-3) = 3
2010-02-19T10:35:08+01:00
A) 2*(½)² -4= 2*¼ - 4 =½ - 4= -3½

b)[½*(-4)+ 2*½]* (-3)=( -2+1)*(-3)=-1*(-3)=3

* oznacza mnozenie
2010-02-19T11:00:29+01:00
A)2*0.5*0.5-4=0.5-4=-3.5

b)[0.5*(-4)+2*0.5]*(-3)=(-2+1)*(-3)=(-1)*(-3)=3

*-mnożenie
0.5-inaczej 1/2